2018
DOI: 10.1017/s0016756818000493
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of early Mesozoic diabase units in southwestern China: metallogenic and tectonic implications

Abstract: Online supplementary material: Figures S1 and S2 Figure S1. Magma oxygen fugacity during the formation of Hawaiian ocean island basalt (OIB; Jackson et al. 2012), Neoproterozoic mafic rocks of the Yangtze Block (Zhou et al. 2006) and the Badu diabase samples analysed during this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 126 publications
(155 reference statements)
1
9
0
Order By: Relevance
“…We interpret the NE-to NNE-verging thrusts and related fault-propagation anticlines in the middle and northern parts of the ST as D 1 2 deformation. The timing of D 1 2 deformation is constrained by U-Pb ages of diabase intrusions (Qiu et al, 2019;Yang et al, 2018) and our LA-ICP-MS results of detrital zircon. In the Baduwei area, early stage 249 Ma diabase is folded with the anticline and late stage 187 Ma diabase truncates the anticline (Qiu et al, 2019).…”
Section: Deformational Sequencementioning
confidence: 82%
See 3 more Smart Citations
“…We interpret the NE-to NNE-verging thrusts and related fault-propagation anticlines in the middle and northern parts of the ST as D 1 2 deformation. The timing of D 1 2 deformation is constrained by U-Pb ages of diabase intrusions (Qiu et al, 2019;Yang et al, 2018) and our LA-ICP-MS results of detrital zircon. In the Baduwei area, early stage 249 Ma diabase is folded with the anticline and late stage 187 Ma diabase truncates the anticline (Qiu et al, 2019).…”
Section: Deformational Sequencementioning
confidence: 82%
“…10.1029/2020TC006552 3 of 24 Qiu et al, 2019). LS = Lhasa Block, QD = Qaidam Block, QS = Qamdo-Simao Block, QT = Qiangtang Block, SG = Songpan Ganzi accretionary complex, WB = West Burma.…”
Section: Phanerozoic Tectonic Events In South Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…The fold‐thrust belt is formed by collision of the Indochina and SCBs during the Triassic Indosinian Orogeny (Figure 1; e.g., Duan, Meng, Christie‐Blick, & Wu, 2018; Li et al, 2017; Li, Zhang, Dong, & Johnston, 2014; Qiu et al, 2014, 2015, 2016, 2017). Previous regional structural analyses reveal that the Youjiang fold‐thrust belt experienced at least three episodes of deformation, namely Triassic (Indosinian) top‐to‐north thrusting, Jurassic (Yanshanian) northeast‐directed thrusting, and Cenozoic extensional faulting (Li et al, 2017; Qiu et al, 2016, 2019). Previous studies documented Late Cretaceous to Cenozoic alkaline ultramafic dikes in the region and proposed the origin in an extensional setting (Chen et al, 2009; Liu et al, 2010; Xu et al, 2012; Yang et al, 2018), whereas the relevant extensional structures have not been well identified.…”
Section: Introductionmentioning
confidence: 99%